Basic Immunization Status and Incidence of Measles Among Toddlers in Working Area of Limboto Public Health Center, Gorontalo Regency - Asra wati Katili; Sri Andriani Ibrahim; Rini Wahyuni Mohamad (Medical and Health Journal, 2026)
Measles (campak) is a contagious disease that remains a health problem among toddlers and contributes to high morbidity and mortality rates in children. Globally, measles cases increased from 170,000 cases in 2022 to over 320,000 cases in 2023, with deaths occurring mainly in children who did not receive complete immunization. This condition indicates that basic immunization plays an important role in measles prevention. In Gorontalo Province, measles and rubella cases are still found in several districts/cities, with Gorontalo Regency having the highest number of cases. One of the preventive efforts is the provision of complete basic immunization to enhance immunity against the disease. This study aimed to determine the relationship between basic immunization status and the incidence of measles in toddlers in the working area of Limboto Health Center, Gorontalo Regency.This study was a quantitative study with an analytic observational design using a cross-sectional approach. The study population consisted of all toddlers in the working area of Limboto Health Center, Gorontalo Regency, with a total sample of 60 toddlers taken using a total sampling technique. The research instrument used a checklist sheet. Data analysis was conducted univariately and bivariately using the Chi-Square test. The study results showed that there was a relationship between basic immunization status and the incidence of measles in toddlers (p-value < 0.05). The conclusion of this study is that there is a relationship between basic immunization status and the incidence of measles in toddlers. Therefore, it is recommended that healthcare workers increase education for parents and improve complete basic immunization coverage as a preventive measure against measles in toddlers.